(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2023)
In the method of limit states, the coefficient of working conditions must take into account all the features of the work and operation of structures. In the code editions, the scale of these coefficients was regularly reviewed and supplemented. Probabilistic aspects of substantiating the coefficients of the working conditions were developed by researchers of the building structure’s reliability. The interpretation of the constructive correction as an experimental analog of the coefficient of working conditions was achieved by full-scale tests of industrial buildings structures. The analysis of the reliability of compressed-bent elements and statically uncertain systems determined the additional coefficients of the working conditions. The article contains a systematic analytical review of normative documents and scientific publications with an analysis of the evolution of steel structure design codes in terms of changes in the coefficient of working conditions and the involvement of research, experimental and statistical data.